Soybean [Glycine max (L.) Merrill.] seed quality under different production environments, storage conditions and seed invigoration using humic acid - Weerasekara, Weerasekara Mudiyanslage Indika (2022)
The government of Sri Lanka has targeted to increase the production of soybean by the area cultivated. This target was unable to be achieved due to lack of supply in good quality seeds at time of planting. Currently, seed production is only carried out in a single location in Sri Lanka, hence new areas for seed production are required. Seed quality is influenced by both the pre-and post-harvest factors. However, effect of pre harvest production environments on seed quality has not yet been clarified. Therefore, the aim of the first study was to determine the effect of seed production environment on seed development, maturation, and subsequent seed quality. The experiment was conducted at six production environments, three locations [Alutarama (ALU), Polonnaruwa (POL) Mahailuppalama (MI)] over two planting cycles (P1, P2). Seed development and maturation, seed and seedling quality characteristics were evaluated at five reproductive (R6, R7, R8, R8+5 and R8+10) maturity stages. The study infers that production environment at the late reproductive (LR) stage (R6-R8) was critical in determining the seed quality. If the LR coincides with more than 100 mm of rainfall or 75% of relative humidity considered as wet environment, otherwise considered as dry. A longer duration was required for the seeds to mature, around 27.5 days, if the LR stage coincided with wet environment (P1 ALU, P2 ALU P2 POL), in contrast to only 17.5 days in dry environment (P1 MI, P1 POL, P2 MI). Seed lots from dry environment during LR stage surpassed the minimum quality standards (75% final germination) at maturity stage R7 onwards, while this only occurred at maturity stage R8 for wet environments. Soybean seeds with minimum quality standards can be produced in all three locations provided harvesting is done at the correct LR stage. However, the quality of the seeds upon storage may differ due to the influence of the production environment. In the second experiment, full mature stage (R8) seeds were obtained from six environments, and upon drying, seeds were stored over one-year period in two different conditions, ambient (24.6 - 33.8 °C, RH 37-88%) and modified storage condition (20 °C ± 2°C, RH 60-70%). The quality of the stored seeds was evaluated at different storage periods (0, 2, 4, 6, 8, 10, 12 months) to monitor the rate of deterioration. Seeds were subjected to germination and vigor test, antioxidant enzyme activities, and malondialdehyde content. Seed lots that matured in dry environments maintained minimum quality standards for over 12 months under modified storage conditions while only 8 months of storage was possible in ambient condition. A slower rate of reduction was obtained in antioxidant capacity for seeds stored under modified conditions compared with ambient. Thus, modified store is recommended with comparatively low construction (1/3) and running (1/4) cost compared with cold storage. Despite the improvement in storability, decline in seed vigour during storage is inevitable due to ageing. The ageing effects can be alleviated, through seed priming. Thus, the third experiment investigated the effects of Humic acid (HA) (an environmentally safe priming agent) on activities of antioxidant enzymes and lipid peroxidation along with the consequences on seed germination in naturally aged soybean seed. Seed lot that was removed from a 12-month storage under ambient condition with 60±5% germination was primed using distilled water or 0.2 g/L HA solution at 25 °C for 1, 3, 5 and 7 h with non-primed dry seeds as control, resulting in nine treatment combinations. Laboratory and field experiments were carried out to test for the best priming treatment to improve seed germination and seedling vigour. HA priming for 5h mitigated the adverse effect of seed deterioration on germination-related traits by increasing the antioxidant enzyme activity [catalase (CAT) and peroxidase (POD)] and reducing malondialdehyde (MDA) content. In conclusion, soybean seeds can be produced above the minimum quality standard in P1 at MI and POL by managing planting time (from January to March and in P2 at ALU, POL and MI from June to August and can be stored for 8 months under modified storage condition. Overall findings from this study can be used to increase soybean seed availability at time of planting.